Assessment of Emotional Intelligence Levels among Students of a Public Medical College of Pakistan amidst the Crisis of Covid-19 Pandemic - Umaira Ali, Umaira Ali; Shahroz Ansar, Shahroz Ansar; Syed Arshad Sabir, Syed Arshad Sabir (Journal of Rawalpindi Medical College, 2022)
ABSTRACT Purpose Aim of the study was to determine the standards of emotional intelligence among students of Rawalpindi Medical University, Rawalpindi. Method A cross-sectional study, employing the use of a self-made online questionnaire, was carried out among the students of Rawalpindi Medical University’s 1st year to final year MBBS. Convenience sampling was used to collect data, which was subsequently entered into Statistical Package for the Social Sciences (SPSS) version.25 for analysis. Results The average value of emotional intelligence was calculated to be 54.34% ±13.89 SD; mean values for emotional awareness, emotional management and social awareness were found to be 65.15% ±12.6 SD, 51.12% ±12.12 SD and 48.4% ±17.39 SD respectively. Conclusion The emotional intelligence of the students amidst the Corona virus pandemic had a noticeably lower value compared to the values determined previously in other studies in the absence of such pandemic. This result points towards the role of pandemic-induced stress in the apparent decrease of emotional intelligence.